Ekati Diamond Mine™ processed kimberlite reclamation ... - Reid, Neil B.; Naeth, Anne (The University of British Columbia, 2009)
The option to establish a vegetation cover over a rock cover to stabilize processed kimberlite tailings after diamond extraction has prompted revegetation research at the Ekati Diamond Mine™ in the Canadian subarctic barrenlands. Laboratory testing has shown coarse texture, no organic component and lack of available macronutrients to be the principal limitations to plant colonization. This study aims to ameliorate these plant growth limitations to establish a permanent self-sustaining vegetation cover on the Ekati kimberlite tailings containment area, stabilizing the surface materials and promoting natural colonization by the surrounding tundra vegetation. With the addition of structural improving and nutrient providing amendments, plant growth on these kimberlite tailings has shown promise. Successful amendment combinations have included peat moss or papermill waste in combination with biosolids from the mine site and/or fertilizer. ...